Nonoperative Treatment of Select Lateral Compression Type II Pelvic Ring Injuries (OTA/AO 61B2.2) Results in a Low Rate of Radiographic Displacement. Issue 1 (January 2022) - Gibbs, Stephen; Colcord, Madison; Curtin, Patrick; Roomian, Tamar; Seymour, Rachel; Phelps, Kevin; Kempton, Laurence; Hsu, Joseph; Sims, Stephen; Bosse, Michael; Swart, Eric; Karunakar, Madhav
Abstract : Objectives: To quantify radiographic outcomes and to identify predictors of late displacement in the nonoperative treatment of lateral compression type II (LC-2) pelvic ring injuries. Design: Retrospective review. Setting: Two Level 1 trauma centers. Patients/Participants: Thirty eight patients 18 years of age or older with LC-2 pelvic ring injuries were included in the study. Intervention: Nonoperative treatment. Main Outcome Measurements: Crescent fracture displacement (CFD) was measured on initial axial computed tomography scan. Change in pelvic ring alignment was measured by the deformity index, simple ratio, and inlet and outlet ratios on successive plain radiographs. Results: Patients in this study had minimally displaced LC-2 pelvic ring injuries, with median initial CFD of 2 mm and median initial deformity index of 2%. No patients had a change of more than or equal to 10 percentage points in deformity index over the treatment period, but small amounts of displacement were seen on the other ratios. No patients initially selected for nonoperative treatment converted to operative treatment. No radiographic predictors of late displacement were identified. Bilateral pubic rami fractures and the presence of a complete sacral fracture ipsilateral to the crescent fracture were not associated with late displacement. Conclusions: A spectrum of injury severity and stability exists in the LC-2 pattern. Nonoperative treatment of LC-2 injuries with low initial deformity and CFD results in minimal subsequent displacement. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.